Historical Cost and Fair Value: Advantages, Disadvantages, Application - Tkachuk, Natalia V. (Journal of History Culture and Art Research, 2019)
The purpose of the study is to identify the scope of application of historical cost and fair value accounting. Historical cost is the purchase price of an asset acquired by a company. Fair value accounting is based on the current market situation as of the current date. Each type of valuation can be conditionally defined as subjective. However, either historical cost or fair value can be used to form the reporting indicators necessary for key users and stakeholders. The study is based on the analysis of fundamental accounting assumptions (static and dynamic balance-sheet), research papers on accounting, and the legislation of the Russian Federation governing the business activities of legal entities. The study resulted in a logical basis for the use of both fair value and historical cost in producing reporting data, as well as in finding solutions to the problem of their combined use in a single statement. Fair value is necessary to characterize the returns on investments and financial position of a company (static balance-sheet), and historical cost is necessary to calculate returns from ongoing business operations (dynamic balance-sheet).